PERUBAHAN ANATOMI STOMATA DAUN LILI TRUMPET (Lilium longiflorum) SETELAH PEMAPARAN RADIASI SINAR X - Dwipayani Lestari, Ni Kadek; Astarini, Ida Ayu; Oka Nurjaya, I.G.M (Metamorfosa: Journal of Biological Sciences, 2013)
Lily (L. longiflorum) is one of 280 genus of liliaceae family. Variation on flower colour, growth habit, flowering period (shelf life) is very limited in Indonesia, so that plant breeding techniques are required to obtain a wide variety of plants. Physical mutation, radiation with X rays were employed in this study. The aim of this study is to find out the effect of X-ray exposure on lily’s leaves stomata anatomy. Lily seeds were grown in vitro and seedlings were exposed to X ray. This study employ CRD (completely randomized design) with four dose exposure (0 krad, 5 krad, 7,5 krad dan 10 krad) and 10 replicates each dose. Results show that to X ray causing reduction in stomata’s length, stomata amount, index, density of stomata that occurs randomly, compared to control.
Keywords: lily, tissue culture, X rays, stomata